1998
DOI: 10.1016/s0022-2275(20)32516-5
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal lipid accumulation from oxidized low density lipoprotein is correlated with hypertrophy of the Golgi apparatus and trans-Golgi network

Abstract: Lipid accumulation within macrophages is a major sequelae of atherosclerosis. Much of this lipid accumulation occurs within large, swollen lysosomes. We analyzed lipid accumulation in cultured macrophages using oxidized or acetylated low density lipoprotein (LDL) as the loading agent. Pigeon macrophages incubated for 48 h with mildly oxidized pigeon LDL (TBARS ‫؍‬ 5-10 nmol/mg protein) showed significant increases in cellular cholesterol compared with untreated controls. Forty-eight percent of the increased ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 53 publications
2
5
1
Order By: Relevance
“…This may be explained by the fact that they measured the distribution of all cholesterol in the cell, whereas we measured only the radiolabeled cholesterol delivered by oxidized LDL. Our conclusions also differ from those of Yancey et al (26,49), who reported that mouse peritoneal macrophages stored most of their oxidized LDL-derived cholesterol (71%) within cytoplasmic inclusions. However, the LDL used by this group was only mildly oxidized, and would therefore be more susceptible to lysosomal degradation.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the fact that they measured the distribution of all cholesterol in the cell, whereas we measured only the radiolabeled cholesterol delivered by oxidized LDL. Our conclusions also differ from those of Yancey et al (26,49), who reported that mouse peritoneal macrophages stored most of their oxidized LDL-derived cholesterol (71%) within cytoplasmic inclusions. However, the LDL used by this group was only mildly oxidized, and would therefore be more susceptible to lysosomal degradation.…”
Section: Resultscontrasting
confidence: 99%
“…Although it has previously been reported that the apoB component of oxidized LDL accumulates in the lysosomes of macrophages (32), there are conflicting reports regarding the lysosomal accumulation of cholesterol in oxidized LDL-loaded cells (23,24,26,29,(48)(49)(50). Therefore, we investigated the subcellular distribution of cholesterol in oxidized LDL-loaded cells both before and after incubation with HDL 3 .…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the size of the hydrolysisresistant pool increased over time, and the FC generated from oxLDL CE in THP-cells, unlike that generated from acLDL, was not readily transported to the plasma membrane and released. This increase in hydrolysis resistance is consistent with our earlier observation that FC initially builds up in lysosomes, but continued lipid accumulation produces lysosomal CE accumulation (21,50).…”
Section: Clearance Of Acldl and Oxldl Cholesteryl Estersupporting
confidence: 92%
“…Another possibility, consistent with a delay in inhibition of hydrolysis, is that fusion of vesicles carrying enzymes from the trans-golgi network (TGN) with lipid-containing lysosomes becomes compromised. Consistent with this, our previous studies demonstrated accumulation of acid phosphatase activity in the TGN of THP-1 and pigeon macrophages loaded with oxLDL (50). Also consistent with this hypothesis, Lougheed et al (51) showed that oxLDL was localized to lysosomes with decreased density.…”
Section: Clearance Of Acldl and Oxldl Cholesteryl Estersupporting
confidence: 81%
“…( 107 , 108 , 109 ) Uptake of oxLDL through the scavenger receptors, CD36 or SR‐A, results in trafficking of oxLDL to the lysosome, where it gets trapped and cannot be exported out of the lysosome. ( 107 , 108 , 110 ) Unlike the LDLR pathway for cholesterol accumulation, the scavenger receptor pathway does not possess a negative feedback loop, leading to rapid accumulation of oxLDL in KC lysosomes and triggering hepatic inflammation. ( 107 , 108 , 110 , 111 ) Experiments in mouse models with scavenger receptor knockout/inhibition, or alleviation of lysosomal cholesterol accumulation, have shown improvement in the hepatic inflammation characteristic of NASH.…”
Section: Mechanisms Of Cash Developmentmentioning
confidence: 99%